MENINGKATKAN KEOTENTIKAN KURIKULUM SEKOLAH ISLAM: KETERLIBATAN GURU, PRAKTIK SUPERVISI, DAN PENDAMPINGAN PARTISIPATIF - Ahmad Musaddad (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study examines how Islamic madrasah curricula are often administratively replicated without embedding Islamic values or local wisdom. Using an explanatory sequential mixed-methods design, we surveyed 64 teachers and curriculum coordinators, then conducted 12 in-depth interviews. Quantitative analyses (descriptive statistics, Pearson correlation, simple regression) revealed that 78% of documents received only superficial identity changes and only 27% of teachers participated actively. Teacher engagement correlated strongly with document originality (r = 0.62; p < 0.01), while supervisory effectiveness explained 28% of quality variation. Qualitative themes highlight teachers' technical unpreparedness, viewing curriculum as an administrative burden, and a need for on-site case-based coaching. We propose a participatory mentoring model combining on-site training and document review to boost teachers' technical capacity and foster authentic, reflective, context-relevant curricula. Recommendations focus on sustained supervisory policy and co-design of curricula by teachers and supervisors.